2016
DOI: 10.1021/acsami.6b08707
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hemocompatibility of Multilumen Catheters via Nitric Oxide (NO) Release from S-Nitroso-N-acetylpenicillamine (SNAP) Composite Filled Lumen

Abstract: Blood-contacting devices, such as intravascular catheters, suffer from challenges related to thrombus formation and infection. Nitric oxide (NO) is an endogenous antiplatelet and antimicrobial agent. Exogenous release of NO from various polymer matrices has been shown to reduce thrombosis and infection of/on implantable medical devices. However, the clinical applications of such materials have been hindered due to factors such as NO donor leaching and thermal instability. In this study, a novel approach is dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 71 publications
6
54
0
Order By: Relevance
“…The incorporation of SNAP in medical grade polymers have been shown to be hemocompatible and possesses stability during long-term storage at room temperature and physiological conditions [63, 72, 73]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of SNAP in medical grade polymers have been shown to be hemocompatible and possesses stability during long-term storage at room temperature and physiological conditions [63, 72, 73]. …”
Section: Resultsmentioning
confidence: 99%
“…Another report has also shown that hydrophobic polymers with SNAP have extended NO-release at physiological levels (up to 20 days) [70]. Furthermore, the incorporation of SNAP in medical grade polymers are not only hemocompatible and biocompatible but also stable during long-term storage (6 months) at room temperature [63, 72, 73]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we designed a DBCO-capped NO-generating compound for surface engineering. As is well studied in previous work, the transition metal ion Cu(II) has excellent glutathione peroxidase- (GPx-) like activity [ 47 , 48 ], which can catalytically generate NO from both endogenous and synthetic S-nitrosothiols (RSNOs) by decomposing them in the presence of reduced glutathione (GSH). In order to immobilize Cu ions, a cyclen DOTA (1,4,7,10-tetraazacyclododecane- N , N ′, N ″ , N ‴ -tetraacetic acid) was conjugated with a DBCO group ( Figure 4(a) and Figure S4 ) [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…To extend the NO release time, Hopkins et al designed a highly stable NO-releasing coating by covalently attaching SNAP with poly(dimethylsiloxane) (PDMS) (Hopkins et al, 2018 ). Previous studies demonstrated that SNAP-based polymers have exhibited significant leaching of SNAP, which will result in non-localized NO release (Brisbois et al, 2016 ). Through tethering to PDMS, SNAP leaching into surrounding environment was prevented and allowed for lengthened potency.…”
Section: No-releasing Coatingsmentioning
confidence: 99%